CAD techniques for the electromagnetic design of monolithic millimetre-wave integrated circuits - Sánchez-Hernández, David A.; Karacaoglu, Ulun; Gokdemir, Tacar; Khalid, Ata H.; Rezazadeh, Ali A.; Ferrando-Bataller, Miguel; de Reyes, Elias Los (My University, 1997)
It is well known that mm-waves have an important role to play in the rapid expansion of mobile and personal communications. MMIC technology is an important factor since it can provide a means of mass producing the user terminal RF subsystems. Millimetre-wave integrated circuits do not yet however offer the high packing density and functionality which is now possible for lower frequency applications where lumped elements are used. This problem is influenced most of all by the extreme modelling difficulties encountered at frequencies above 30 GHz. This paper reviews the current state-of-the-art for CAD techniques used in MMIC design. It describes some limitations of the standard Smart™ library approach and looks at the application of commercial electromagnetic simulators in the design of both microstrip and CPW circuits.
Keywords: Amplifier; Annular resonator; Circuit design; Circuit library; Computer aided design; Electrical simulation; Microstrip line; Microwave integrated circuit; Millimetric wave; Modeling; Monolithic integrated circuit; Transceiver